Analisis Sistem Informasi Pengelolaan Data Barang Berbasis Web Menggunakan Metode Agile - Mohamad Fadlan Jabbar (PT Jurnal Cendekia Indonesia, 2025)
In this study, the Agile method, which is a primary approach in software development, is used to develop and analyze a web-based information system for managing inventory data. The need for a system that can replace manual recording methods—which often lead to data inaccuracies, delays in information retrieval, and low operational efficiency—is the foundation of this research. The system is designed to assist in various inventory management tasks such as recording incoming and outgoing goods, managing stock levels, generating reports, and tracking transaction history in real time. Agile methodology ensures that development proceeds in an iterative, flexible manner and remains focused on user needs that may change over time. The process begins with identifying user requirements, followed by system design, coding, testing, and regular evaluation of system functionality. The results show that the Agile method improves the speed and accuracy of system development and enhances interaction between developers and end users. The web-based information system increases accessibility, improves data accuracy, and supports better decision-making in inventory management. Therefore, this system is expected to serve as an efficient and flexible technological tool to assist in managing inventory data across various business sectors or organizations.